INTERCULTURAL DIALOGUE IN THE CONTEXT OF UKRAINIAN UNIFICATION - Afanasieva, Liudmyla; Muzja, Eugene; Koleva, Krasimira; Oleksenko, Roman (Київський національний університет імені Тараса Шевченка, 2017)
The process of intercultural dialogue is a long-term phenomenon. It means that the intercultural dialogue is acomplex, contradictory and ambivalent factor of the present, which is a complex of many components and it depends on the bninfluence of some systemic factors.The dialogue includes spiritual and moral aspects that contribute to the establishment of understanding and theconsistency not only at the interpersonal level, but the intercultural communication. The main category that defines the essence ofthe cultural dialogue is the understanding that leads to the knowledge of the inner world of culture ant its value significance. Thedialogue, as a universal phenomenon, fixes the constructive side of cultural interaction, it is an integrator of cultural completeness,demonstrates the impossibility of the culture beyond the dialogue.In the context of globalization, characterized by tendencies towards cultural unification and cultural isolation, theintercultural dialogue is an important factor for cultural integrity and its preservation. This is largely attributable to the multiculturalspace where ethnic cultures produce models of dialogue that include both universal foundations and their own cultural peculiarities.Spiritual and cultural integrity is the protection of the spiritual, moral, cultural foundations of society's life, which level is determined bythe readiness for dialogue, in other words, the participants’ ability to understand each other in the cultural process, to recognize thevalue of another culture. In the multicultural regions of Ukraine, the dialogue acts as a key factor in providing spiritual and culturalsafety, also it helpstosustain the functional and reproductiveaspects in the cultures of all national groups in the region to preservetheethnic identity.Summarizing our culture-specific elements, we can conclude that the intercultural dialogue belongs to the list of fundamentallycorrected phenomena, that is, on the one hand, it should be givenappropriate value and shown respect according to the objective datadue to the historical preconditions, and on the other - to realize their extent imperfection, partiality, and the need for adjustment andoptimization from the standpoint of “Appropriate”. Firstly, this“Appropriate” is the equality of various cultural assets in the context ofgeneral civilization value, and secondly, the sovereign right to borrow and assimilate any cultural norms from another culture, and todeny such a necessity due to the inconsistency of other cultural norms with the imperatives of their own culture.The variety and complexity, where the dialogue has its own role in the context of modern culture, create new challenges forresearchers. The dimension of civilization development, when the human mind managed to fix and understand the cultural-historicalprocess, is replaced by a rapid change in cultural space. In this regard, new synergetic methodologies are needed to build effective,practically valuable concepts of culturaldialogue interaction.Key words: consensus, tolerance, intercultural communication, mutual understanding.

У ході дослідження було встановлено, що діалог культур, з одного боку, забезпечує вільний розвиток функціонування всіх культур, а з іншого, сприяє процесу їх взаємодії, взаємовпливу і взаємозбагачення. Виявленонеобхідність дослідження міжкультурного діалогу як фактора узгодження різних інтересів, що все частіше виступаєєдино можливим способом виживання людства у зв’язку з суперечливими, кризовими процесами, що протікають всучасному суспільстві, головною умовою толерантного вирішення конфліктних ситуацій. Встановлено, що діалогкультур можливий тільки при певному зближенні їх культурних кодів, наявності або виникненні загальної ментальності.З’ясовано, що умовою продуктивного діалогу є довіра, а довіра з'являється лише там, де відкрито і достатньо ясно доспіврозмовника доноситься наше розуміння про його і наші позиції й цінності. Визначено, що діалог культур – цепроникнення в систему цінностей тієї чи іншої культури, що здійснюється через повагу до них, подолання стереотипів,синтез самобутнього і інонаціонального, що веде до взаємозбагачення і входження в світовий культурний контекст.З’ясовано, що в діалозі дуже важливо побачити загальнолюдські цінності взаємодіючих культур. Виявлено, щонаціональний рівень міжкультурного діалогу є значно складнішим, ніж етнічний, так як охоплює не тільки ціннісний, а йполітико-правовий, соціо-економічний та ідеологічний аспекти.Ключові слова: консенсус, толерантність, міжкультурна комунікація, взаєморозуміння.
МІЖКУЛЬТУРНИЙ ДІАЛОГ В КОНТЕКСТІ ЄДНАННЯ УКРАЇНИ